Revelation, Not Revolution: Queer Poetry’s Political Life, as Read through Robert Duncan’s Late Anarchism - Eric Keenaghan (Sillages Critiques)
Robert Duncan, a homosexual American poet, had conflicted and often self-contradictory relationships with gay liberation and sexual identity politics. Nonetheless, his ideas about eroticism’s centrality to poetic composition could help us reimagine poetry’s potential and its limits for addressing crises now affecting and dehumanizing queer persons.